Gender Politics in To the Lighthouse - Ordu, Ferhat; KARAKAŞ, Murat (Journal of History Culture and Art Research, 2015)
Gender Politics in To the Lighthouse Abstract To the Lighthouse is one of the most influential works of Virginia Woolf and it is inevitable to find traces of Feminism in any of Woolf’s works. From the perspective of Feminist Criticism, this article tries to solve the gender identity problem in To the Lighthouse and focuses upon the struggle of the Modern woman against the dominant Patriarchal male characters and submissive female characters trying to find her own way out.